Vibration therapy as an intervention for trochanteric hip fractures – A randomized double-blinded, placebo-controlled trial - Ronald Man Yeung Wong; Pui Yan Wong; Chaoran Liu; Chun Sing Chui; Wing Hong Liu; Ning Tang; James Griffith; Ning Zhang; Wing Hoi Cheung (Journal of Orthopaedic Translation)
Background: Hip fractures are one of the most serious forms of fragility fractures. Low-magnitude high-frequency vibration (LMHFV) is a biophysical intervention that provides non-invasive, systemic mechanical stimulation. The objectives of this study were to investigate the efficacy of LMHFV in trochanteric hip fracture elderly patients to (i) accelerate trochanteric fracture healing and (ii) improve clinical and functional outcomes. Methods: A randomized double-blinded, placebo-controlled clinical trial was conducted. Participants were randomly assigned into LMHFV or placebo intervention for 14 days. Primary outcome assessments were fracture healing assessed with CT scan and X-rays. Dual X-ray Absorptiometry (DXA) scan was performed to assess bone mineral density change. Secondary outcome assessments were clinical and functional outcomes with quadriceps muscle strength, balancing ability, handgrip strength, Time Up and Go (TUG) test, quality of life outcomes, pain, falls, and mortality. Results: 237 patients were screened for eligibility by the inclusion and exclusion criteria. 62 patients were recruited and randomly assigned to placebo group (n = 32, mean age: 83.6 ± 7.0 years, women: 71.9 %) or LMHFV group (n = 30, mean age: 81.5 ± 5.7 years, women: 73.3 %). For fracture healing, CT scan at 6 weeks showed improved osseous union for the LMHFV group at 71.5 ± 19.4 % compared to placebo group at 58.8 ± 30.5 %, but no statistical significance detected. X-rays showed fractures healed at 12 months. LMHFV group had significantly higher quadriceps muscle strength compared to placebo group on affected leg using maximum reading (week 26: 8.8 ± 3.6 kg vs. 6.1 ± 4.1 kg; p = 0.011) and average reading (week 26: 8.0 ± 3.7 kg vs. 5.2 ± 3.3 kg; p = 0.008) amongst 3 trials. The balancing ability test could not be performed in most of the subjects at the baseline measurement. However, from week 6 to week 26, LMHFV group had significantly improved balancing compared to placebo group for overall stability index (week 26: 1.6 ± 1.1 vs. 3.4 ± 2.6; p = 0.006), anteroposterior stability index (week 26: 1.1 ± 0.7 vs. 2.1 ± 1.9; p = 0.048) and medial-lateral stability index (week 26: 0.9 ± 0.7 vs. 2.2 ± 2.2; p = 0.008). There was a significant increase in success in performing TUG test in LMHFV group from baseline (13.3 %) to 26 weeks (57.1 %) (p = 0.004). Quality-of-life outcomes by SF-36 showed LMHFV group had a significant improvement at a score of 62.1 ± 18.9 compared to control group at a score of 48.5 ± 18.9 after adjusting for the baseline measurement (p = 0.044). Conclusion: A short duration of LMHFV during in-patient stay can improve clinical outcomes and can potentially be incorporated as a practical measure during the recovery of fragility hip fractures. The translational potential of this article: 14 days of LMHFV treatment is generally within the common in-patient stay period for hip fracture patients and therefore can potentially be incorporated into clinical practice with physiotherapy to facilitate recovery of hip fracture patients. Clinical trial registration number: NCT04063891.